Distribution of Voltage Gated Sodium Channel (VGSC) Gene Mutational Variation And Acetylcholinesterase-1 (ACE-1) as A Marker For Insecticide Resistance In Culex spp. Mosquitoes In Surabaya - Akbar Panjinegara, Muhammad; Basuki, Sukmawati; Husada, Dominicus; Pusarawati, Suhintam (CV. Publikasi Indonesia, 2024)
Culex spp. is a vector for Japanese Encephalitis (JE) and filariasis in Indonesia. JE is caused by Japanese Encephalitis Virus (JEV). JEV attacks the central nervous system and causes inflammation of the brain, lifelong disability, and even death. Filariasis is a chronic infectious disease that can cause permanent disability. Transmission of JE and filariasis can increase due to the density of Culex spp mosquitoes. The purpose of this study was to identify the distribution of mutation variations in the Voltage Gated Sodium Channel (VGSC) and acetylcholinesterase-1 (ace-1) genes in Culex spp. mosquitoes in Surabaya. Mutation variations of the VGSC Culex spp. gene show that there are three genotypes, namely wildtype (LL), heterozygous (LS, FS), and homozygous (FF, SS). Heterozygous (FS) and homozygous (FF, FS) genotypes caused by point mutations in codon 1014 of the VGSC gene are found in the Culex spp. mosquito population in Surabaya. Heterozygous (LF) genotype was not detected in the Culex spp. mosquito population in Surabaya. Another study in Nigeria showed that homozygous/FF genotypes (45.1%) were more prevalent than heterozygotes/LF (36.3%) and wildtypes/LL (18.6%).